Hubungan Penggunaan Instagram dengan Pemenuhan Kebutuhan Informasi Warga Dayeuhkolot Kabupaten Bandung - Ristianto; Rini Rinawati (UNISBA Press, 2024)
Abstract. This research is entitled The Relationship between Instagram Use and Fulfilling the Information Needs of Dayeuhkolot Residents, Bandung Regency